Infrahepatic Inferior Vena Cava Clamping Reduces Blood Loss during Liver Transection for Cholangiocarcinoma - Natwutpong Leeratanakachorn; Vor Luvira; Theerawee Tipwaratorn; Suapa Theeragul; Apiwat Jarearnrat; Attapol Titapun; Tharatip Srisuk; Supot Kamsa-ard; Ake Pugkhem; Narong Khuntikeo; Chawalit Pairojkul; Vajarabhongsa Bhudhisawasdi (International Journal of Hepatology)
Background. Major hepatectomy is the mainstay of the treatment for cholangiocarcinoma. Infrahepatic inferior vena cava (IVC) clamping is an effective maneuver for reducing blood loss during liver transection. The impact of this procedure on major hepatectomy for cholangiocarcinoma is unknown. This study evaluated the effect of infrahepatic IVC clamping on blood loss during liver transection. Methods. Clinical and pathological data were collected retrospectively for 116 cholangiocarcinoma patients who underwent major hepatectomy between January 2015 and December 2016, to investigate the benefit of infrahepatic IVC clamping. Two of five surgeons adapted the policy performing infrahepatic IVC clamping during liver transection in all cases. Patients, therefore, were divided into those (n=39; 33.6%) who received infrahepatic IVC clamping during liver transection (C1) and those (n=77; 66.4%) who did not (C0). Results. The patients’ backgrounds, operative parameters, and extent of hepatectomy did not differ significantly between the 2 groups, except for gender. A significantly lower blood loss (p=0.028), blood transfusion (p=0.011), and rate of vascular inflow occlusion requirement (p<0.001) were observed in the C1 group. The respective blood losses in the C1 group and the C0 group were 498.9 (95% CI: 375.8-622.1) and 685.6 (95% CI: 571-800.2) millilitres. Conclusions. The current study found infrahepatic IVC clamping during liver transection for cholangiocarcinoma reduces blood loss, blood transfusion, and rate of vascular inflow occlusion requirement.